Invasive macroalgae exert stronger effects than elevated CO₂ on seagrass (Posidonia oceanica) seedling performance and associated microbiomes - Iris E. Hendriks; Julia Máñez-Crespo; Clea N. van de Ven; R. Sean Fitzpatrick; Alberto V. Borges; Willy Champenois; Tania Aires; Aschwin H. Engelen; Gerard Muyzer; J. Arie Vonk; Fiona Tomas (Marine Pollution Bulletin, 2026)

Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Spatial differences in the ovine cervical microenvironment at the follicular and luteal phases of the oestrous cycle; Implications for sperm transport - N. Johnston; E. Bini; E. Fitzpatrick; C. Reid; S. Fair (Theriogenology, 2026)

Sensory profile and drivers of liking of grass-fed and total mixed ration butters - Lauren McGuinness; Mark Timlin; Sean A. Hogan; Tom F. O'Callaghan; John P. Murphy; Deirdre Hennessy; Michael O'Donovan; Ellen Fitzpatrick; Kieran McCarthy; E. Dolores O'Riordan; Andre Brodkorb; Emma L. Feeney (Food Quality and Preference, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Long-term air pollution exposure and gait speed decline among older Adults: A longitudinal analysis - Boeun Kim; Anjum Hajat; Amanda J. Gassett; Claire E. Adam; Joel D. Kaufman; Erin O. Semmens; Cindy S. Leary; Annette L. Fitzpatrick (Environmental Research, 2026)

Purification of uranium tetrafluoride using ammonium bifluoride - Kyle R. Foster; Juliano Schorne-Pinto; Ronald E. Booth; Annabelle Husek; Mina Aziziha; Hunter B. Tisdale; Bernie W.N. Fitzpatrick; Hans-Conrad zur Loye; Markus H.A. Piro; Theodore M. Besmann (Journal of Fluorine Chemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Innovative Systems Engineering Solutions for Power-Positive Operations: Navigating the Multi-Constraint Challenges of the SWARM-EX CubeSat Mission - David J. Fitzpatrick; Scott E. Palo (Advances in Space Research, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Proteomic Analysis of Chronic Binge Alcohol-Induced Hippocampal and Anterior Cingulate Cortex Neuroadaptations in Simian Immunodeficiency Virus (SIV)-Infected Female Rhesus Macaques - Taylor Fitzpatrick-Schmidt; Amirsalar Mansouri; Jiri Adamec; Jennifer Klein; Larry Coleman; Kimberly N. Edwards; Liz Simon; Patricia E. Molina; Michael C. Salling; Scott Edwards (Journal of Neuroimmune Pharmacology, 2025)

P07-09 Spatio-temporal multi-omics analysis of lung tissue and matched biofluids identifies circulatory safety biomarkers for monitoring inhaled drug induced lung injury - M.M. Majumder; E. Williams; M.O. Lindvall; A. Jarnuczak; G. Hamm; C. Di Poto; A.A. Iannetta; J.L. Touza; E.L. Allman; E. Miele; J. Lindgren; E. Sand; et al. (Toxicology Letters, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Genomic insights into hybrid zone formation: The role of climate, landscape, and demography in the emergence of a novel hybrid lineage - Constance E. Bolte; Tommy Phannareth; Michelle Zavala‐Paez; Brianna N. Sutara; Muhammed F. Can; Matthew C. Fitzpatrick; Jason A. Holliday; Stephen R. Keller; Jill A. Hamilton (Molecular Ecology, 2024)
Population demographic changes, alongside landscape, geographic and climate heterogeneity, can influence the timing, stability and extent of introgression where species hybridise. Thus, quantifying interactions across diverged lineages, and the relative contributions of interspecific genetic exchange and selection to divergence at the genome‐wide level is needed to better understand the drivers of hybrid zone formation and maintenance. We used seven latitudinally arrayed transects to quantify the contributions of climate, geography and landscape features to broad patterns of genetic structure across the hybrid zone of Populus trichocarpa and P. balsamifera and evaluated the demographic context of hybridisation over time. We found genetic structure differed among the seven transects. While ancestry was structured by climate, landscape features influenced gene flow dynamics. Demographic models indicated a secondary contact event may have influenced contemporary hybrid zone formation with the origin of a putative hybrid lineage that inhabits regions with higher aridity than either of the ancestral groups. Phylogenetic relationships based on chloroplast genomes support the origin of this hybrid lineage inferred from demographic models based on the nuclear data. Our results point towards the importance of climate and landscape patterns in structuring the contact zones between P. trichocarpa and P. balsamifera and emphasise the value whole genome sequencing can have to advancing our understanding of how neutral processes influence divergence across space and time.

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Insights from a community of practice: Integrating human rights in fisheries improvement - Elena M. Finkbeiner; Christopher Giordano; Juno Fitzpatrick; Ashley Apel; Cecilia Blasco; Kathryn H. Dalton; Juan Carlos Jerí; Ines Lopez-Ercilla; Gabrielle E. Lout; Chris Madden; Ivan Martinez-Tovar; Pablo Obregon; et al. (Marine Policy, 2024)

Impact of feeding regimes and lactation stage on sensory attributes of Cheddar cheese - Lauren McGuinness; Mark Timlin; John P. Murphy; Deirdre Hennessy; Ellen Fitzpatrick; Kieran McCarthy; Michael O'Donovan; Tom F. O'Callaghan; Kieran N. Kilcawley; E. Dolores O'Riordan; Andre Brodkorb; Jeremiah J. Sheehan; et al. (Food Research International, 2024)

Retrospective analysis of dog study data from food and color additive petitions - Brenna M. Flannery; Alexandra E. Turley; Njwen Anyangwe; Antonia Mattia; Catherine Whiteside; Steven Hermansky; Heather R. Schaefer; Tina Tyler; Suzanne C. Fitzpatrick (Regulatory Toxicology and Pharmacology, 2023)

Terrestrial carbon isotope stratigraphy of the Eocene–Oligocene transition, Petrockstowe and Bovey basins, Devon, UK - Mohammed S. Chaanda; Stephen T. Grimes; Rhodri M. Jerrett; Mark Anderson; Melanie J. Leng; Meriel E. Fitzpatrick; Gregory D. Price (Proceedings of the Geologists' Association, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

The structure and organisation of an Amazonian bird community remains little changed after nearly four decades in Manu National Park - Ari E. Martínez; José M. Ponciano; Juan P. Gomez; Thomas Valqui; Jorge Novoa; Mariamercedes Antezana; Gabriela Biscarra; Ettore Camerlenghi; Blaine H. Carnes; Renato Huayanca Munarriz; Eliseo Parra; Isabella M. Plummer; et al. (Ecology Letters, 2023)
Documenting patterns of spatiotemporal change in hyper‐diverse communities remains a challenge for tropical ecology yet is increasingly urgent as some long‐term studies have shown major declines in bird communities in undisturbed sites. In 1982, Terborgh et al. quantified the structure and organisation of the bird community in a 97‐ha. plot in southeastern Peru. We revisited the same plot in 2018 using the same methodologies as the original study to evaluate community‐wide changes. Contrary to longitudinal studies of other neotropical bird communities (Tiputini, Manaus, and Panama), we found little change in community structure and organisation, with increases in 5, decreases in 2 and no change in 7 foraging guilds. This apparent stability suggests that large forest reserves such as the Manu National Park, possibly due to regional topographical influences on precipitation, still provide the conditions for establishing refugia from at least some of the effects of global change on bird communities.

Interictal Cognitive Deficits in Migraine Sufferers: A Meta-Analysis - Dion L. Braganza; Lauren E. Fitzpatrick; Mai L. Nguyen; Simon F. Crowe (Neuropsychology Review, 2022)

Elevated Winter Stream Temperatures below Wastewater Treatment Plants Shift Reproductive Development of Female Johnny Darter Etheostoma nigrum: A Field and Histologic Approach - Catherine M. Adams; Dana L. Winkelman; Paula A. Schaffer; Daniel L. Villeneuve; Jenna E. Cavallin; Michael Ellman; Kelvin Santana Rodriguez; Ryan M. Fitzpatrick (Fishes, 2022)
River water temperatures are increasing globally, particularly in urban systems. In winter, wastewater treatment plant (WWTP) effluent inputs are of particular concern because they increase water temperatures from near freezing to ~7–15 °C. Recent laboratory studies suggest that warm overwinter temperatures impact the reproductive timing of some fishes. To evaluate winter water temperature’s influence in the wild, we sampled Johnny Darter Etheostoma nigrum from three urban South Platte River tributaries in Colorado upstream and downstream of WWTP effluent discharge sites. Fish were collected weekly during the spring spawning season of 2021 and reproductive development was determined from histological analysis of the gonads. Winter water temperatures were approximately 5–10 °C greater ~300 m downstream of the WWTP effluent compared to upstream sites, and approximately 3 °C warmer at sampling sites ~5000 m downstream of the effluent discharge. Females collected downstream of WWTP effluent experienced accelerated reproductive development compared to upstream by 1–2 weeks. Water quality, including total estrogenicity, and spring water temperatures did not appear to explain varying reproductive development. It appears that small increases in winter water temperature influence the reproductive timing in E. nigrum. Further investigations into how shifts in reproductive timing influence other population dynamics are warranted.

A critical comparison of integral projection and matrix projection models for demographic analysis: Reply - Daniel F. Doak; Ellen Waddle; Ryan E. Langendorf; Allison M. Louthan; Nathalie Isabelle Chardon; Reilly Dibner; Robert K. Shriver; Cristina Linares; Maria Begoña Garcia; Sarah W. Fitzpatrick; William F. Morris; Megan L. DeMarche (Ecology, 2022)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Homeless and hungry: food insecurity in the land of plenty - Kevin M. Fitzpatrick; Don E. Willis (Food Security, 2021)

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Contemporary range position predicts the range‐wide pattern of genetic diversity in balsam poplar ( Populus balsamifera L.) - Andrew V. Gougherty; Vikram E. Chhatre; Stephen R. Keller; Matthew C. Fitzpatrick (Journal of Biogeography, 2020)
Aim Patterns of genetic diversity within species’ ranges can reveal important insights into effects of past climate on species’ biogeography and current population dynamics. While numerous biogeographic hypotheses have been proposed to explain patterns of genetic diversity within species’ ranges, formal comparisons and rigorous statistical tests of these hypotheses remain rare. Here, we compared seven hypotheses for their abilities to describe the geographic pattern of two metrics of genetic diversity in balsam poplar ( Populus balsamifera ), a northern North American tree species. Location North America. Taxon Balsam poplar ( Populus balsamifera L.). Methods We compared seven hypotheses, representing effects of past climate and current range position, for their ability to describe the geographic pattern of expected heterozygosity and per cent polymorphic loci across 85 populations of balsam poplar. We tested each hypothesis using spatial and non‐spatial least‐squares regression to assess the importance of spatial autocorrelation on model performance. Results We found that both expected heterozygosity and per cent polymorphic loci could best be explained by the current range position and genetic structure of populations within the contemporary range. Genetic diversity showed a clear gradient of being highest near the geographic and climatic range centre and lowest near range edges. Hypotheses accounting for the effects of past climate (e.g. past climatic suitability, distance from the southern edge), in contrast, had comparatively little support. Model ranks were similar among spatial and non‐spatial models, but residuals of all non‐spatial models were significantly autocorrelated, violating the assumption of independence in least‐squares regression. Main conclusions Our work adds strong support for the “Central‐Periphery Hypothesis” as providing a predictive framework for understanding the forces structuring genetic diversity across species’ ranges, and illustrates the value of applying a robust comparative model selection framework and accounting for spatial autocorrelation when comparing biogeographic models of genetic diversity.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Temperature and telomeres: thermal treatment influences telomere dynamics through a complex interplay of cellular processes in a cold-climate skink - L. J. Fitzpatrick; M. Olsson; L. M. Parsley; A. Pauliny; T. L. Pinfold; T. Pirtle; G. M. While; E. Wapstra (Oecologia, 2019)

Recreational sector is the dominant source of fishing mortality for oceanic fishes in the Southeast United States Atlantic Ocean - Kyle W. Shertzer; Erik H. Williams; Joseph Kevin Craig; Eric E. Fitzpatrick; Nikolai Klibansky; Katie I. Siegfried (Fisheries Management and Ecology, 2019)
Recreational fishing is increasingly recognised as an important source of mortality for marine fish populations. In the United States, estimates of marine recreational catch and effort were recently revised for the time period 1981 and beyond, and for many species, the revised estimates were substantially higher than the original values. Here, the proportion of total landings that came from the recreational sector in the Southeast US Atlantic was quantified. The proportions for 22 oceanic species and for all species combined were computed, using a full time series of landings (1981–2016) and a more recent time series (1999–2016). For the full and recent time series, landings of most species (15/22 and 17/22, respectively) were dominated by the recreational sector. For all species combined, 71% of landings in the full time series were from the recreational sector, and 76% in the recent time series. Trend analysis indicated that most species had a stable or increasing proportion of landings from the recreational sector. In addition, stock assessments were conducted on four species, and the catch revisions increased the estimated scale of abundance and, in some cases, affected stock or fishery status. This work underscores the importance of recreational fishing for marine resource management.

An experimental test of alternative population augmentation scenarios - John A. Kronenberger; Jill C. Gerberich; Sarah W. Fitzpatrick; E. Dale Broder; Lisa M. Angeloni; W. Chris Funk (Conservation Biology, 2018)
Human land use is fragmenting habitats worldwide and inhibiting dispersal among previously connected populations of organisms, often leading to inbreeding depression and reduced evolutionary potential in the face of rapid environmental change. To combat this augmentation of isolated populations with immigrants is sometimes used to facilitate demographic and genetic rescue. Augmentation with immigrants that are genetically and adaptively similar to the target population effectively increases population fitness, but if immigrants are very genetically or adaptively divergent, augmentation can lead to outbreeding depression. Despite well‐cited guidelines for the best practice selection of immigrant sources, often only highly divergent populations remain, and experimental tests of these riskier augmentation scenarios are essentially nonexistent. We conducted a mesocosm experiment with Trinidadian guppies (Poecilia reticulata) to test the multigenerational demographic and genetic effects of augmenting 2 target populations with 3 types of divergent immigrants. We found no evidence of demographic rescue, but we did observe genetic rescue in one population. Divergent immigrant treatments tended to maintain greater genetic diversity, abundance, and hybrid fitness than controls that received immigrants from the source used to seed the mesocosms. In the second population, divergent immigrants had a slightly negative effect in one treatment, and the benefits of augmentation were less apparent overall, likely because this population started with higher genetic diversity and a lower reproductive rate that limited genetic admixture. Our results add to a growing consensus that gene flow can increase population fitness even when immigrants are more highly divergent and may help reduce uncertainty about the use of augmentation in conservation.

Population demography and heterozygosity–fitness correlations in natural guppy populations: An examination using sexually selected fitness traits - Catherine E. Grueber; John L. Fitzpatrick; Alessandro Devigili; Clelia Gasparini; Indar W. Ramnarine; Jonathan P. Evans (Molecular Ecology, 2017)
Heterozygosity–fitness correlations ( HFC s) have been examined in a wide diversity of contexts, and the results are often used to infer the role of inbreeding in natural populations. Although population demography, reflected in population‐level genetic parameters such as allelic diversity or identity disequilibrium, is expected to play a role in the emergence and detectability of HFC s, direct comparisons of variation in HFC s across many populations of the same species, with different genetic histories, are rare. Here, we examined the relationship between individual microsatellite heterozygosity and a range of sexually selected traits in 660 male guppies from 22 natural populations in Trinidad. Similar to previous studies, observed HFC s were weak overall. However, variation in HFC s among populations was high for some traits (although these variances were not statistically different from zero). Population‐level genetic parameters, specifically genetic diversity levels (number of alleles, observed/expected heterozygosity) and measures of identity disequilibrium (g2 and heterozygosity–heterozygosity correlations), were not associated with variation in population‐level HFC s. This latter result indicates that these metrics do not necessarily provide a reliable predictor of HFC effect sizes across populations. Importantly, diversity and identity disequilibrium statistics were not correlated, providing empirical evidence that these metrics capture different essential characteristics of populations. A complex genetic architecture likely underpins multiple fitness traits, including those associated with male fitness, which may have reduced our ability to detect HFC s in guppy populations. Further advances in this field would benefit from additional research to determine the demographic contexts in which HFC s are most likely to occur.

Microsatellite analysis supports the existence of three cryptic species within the bumble bee Bombus lucorum sensu lato - Lorraine McKendrick; Jim Provan; Úna Fitzpatrick; Mark J. F. Brown; Tómas E. Murray; Eckart Stolle; Robert J. Paxton (Conservation Genetics, 2017)

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Quantitative magnetic resonance imaging in patients with cirrhosis: a cross-sectional study - Vijay P. B. Grover; Mary M. E. Crossey; Julie A. Fitzpatrick; Brian K. Saxby; Roberta Shaw; Adam D. Waldman; Marsha Y. Morgan; Simon D. Taylor-Robinson (Metabolic Brain Disease, 2016)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

The importance of plant genotype and contemporary evolution for terrestrial ecosystem processes - Connor R. Fitzpatrick; Anurag A. Agrawal; Nathan Basiliko; Amy P. Hastings; Marney E. Isaac; Michael Preston; Marc T. J. Johnson (Ecology, 2015)
Plant genetic variation and evolutionary dynamics are predicted to impact ecosystem processes but these effects are poorly understood. Here we test the hypothesis that plant genotype and contemporary evolution influence the flux of energy and nutrients through soil, which then feedback to affect seedling performance in subsequent generations. We conducted a multiyear field evolution experiment using the native biennial plant Oenothera biennis . This experiment was coupled with experimental assays to address our hypothesis and quantify the relative importance of evolutionary and ecological factors on multiple ecosystem processes. Plant genotype, contemporary evolution, spatial variation, and herbivory affected ecosystem processes (e.g., leaf decay, soil respiration, seedling performance, N cycling), but their relative importance varied between specific ecosystem variables. Insect herbivory and evolution also contributed to a feedback that affected seedling biomass of O. biennis in the next generation. Our results show that heritable variation among plant genotypes can be an important factor affecting local ecosystem processes, and while effects of contemporary evolution were detectable and sometimes strong, they were often contingent on other ecological factors.

Adult vascular smooth muscle cells in culture express neural stem cell markers typical of resident multipotent vascular stem cells - Eimear Kennedy; Ciaran J. Mooney; Roya Hakimjavadi; Emma Fitzpatrick; Shaunta Guha; Laura E. Collins; Christine E. Loscher; David Morrow; Eileen M. Redmond; Paul A. Cahill (Cell and Tissue Research, 2014)

The basolateral amygdala determines the effects of fear memory on sleep in an animal model of PTSD - Laurie L. Wellman; Mairen E. Fitzpatrick; Mayumi Machida; Larry D. Sanford (Experimental Brain Research, 2014)

Hydrology and climatology at Laguna La Gaiba, lowland Bolivia: complex responses to climatic forcings over the last 25 000 years - SARAH E. METCALFE; BRONWEN S. WHITNEY; KATHARINE A. FITZPATRICK; FRANCIS E. MAYLE; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; DAVID G. MANN (Journal of Quaternary Science, 2014)
Diatom, geochemical and isotopic data provide a record of environmental change in Laguna La Gaiba, lowland Bolivia (17°45′S, 57°35′W), over the last ca. 25 000 years. High‐resolution diatom analysis around the Last Glacial–Interglacial Transition provides new insights into this period of change. The full and late glacial lake was generally quite shallow, but with evidence of periodic flooding. At about 13 100 cal a BP, just before the start of the Younger Dryas chronozone, the diatoms indicate shallower water conditions, but there is a marked change at about 12 200 cal a BP indicating the onset of a period of high variability, with rising water levels punctuated by periodic drying. From ca. 11 800 to 10 000 cal a BP, stable, deeper water conditions persisted. There is evidence for drying in the early to middle Holocene, but not as pronounced as that reported from elsewhere in the southern hemisphere tropics of South America. This was followed by the onset of wetter conditions in the late Holocene consistent with insolation forcing. Conditions very similar to present were established about 2100 cal a BP. A complex response to both insolation forcing and millennial‐scale events originating in the North Atlantic is noted.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Cognitive and Emotional Deficits in Chronic Alcoholics: a Role for the Cerebellum? - Lauren E. Fitzpatrick; Simon F. Crowe (The Cerebellum, 2013)

Lethal Effects of Water Quality on Threatened California Salamanders but Not on Co‐Occurring Hybrid Salamanders - MAUREEN E. RYAN; JARRETT R. JOHNSON; BENJAMIN M. FITZPATRICK; LINDA J. LOWENSTINE; ANGELA M. PICCO; H. BRADLEY SHAFFER (Conservation Biology, 2013)
Biological invasions and habitat alteration are often detrimental to native species, but their interactions are difficult to predict. Interbreeding between native and introduced species generates novel genotypes and phenotypes, and human land use alters habitat structure and chemistry. Both invasions and habitat alteration create new biological challenges and opportunities. In the intensively farmed Salinas Valley, California (U.S.A.), threatened California tiger salamanders ( Ambystoma californiense ) have been replaced by hybrids between California tiger salamander and introduced barred tiger salamanders ( Ambystoma tigrinum mavortium ). We conducted an enclosure experiment to examine the effects habitat modification and relative frequency of hybrid and native California tiger salamanders have on recruitment of salamanders and their prey, Pacific chorus frogs ( Pseudacris regilla ). We tested whether recruitment differed among genetic classes of tiger salamanders (hybrid or native) and pond hydroperiod (seasonal or perennial). Roughly 6 weeks into the experiment, 70% (of 378 total) of salamander larvae died in 4 out of 6 ponds. Native salamanders survived ( n = 12) in these ponds only if they had metamorphosed prior to the die‐offs. During die‐offs, all larvae of native salamanders died, whereas 56% of hybrid larvae died. We necropsied native and hybrid salamanders, tested water quality, and queried the California Department of Pesticide Regulation database to investigate possible causes of the die‐offs. Salamander die‐offs, changes in the abundance of other community members (invertebrates, algae, and cyanobacteria), shifts in salamander sex ratio, and patterns of pesticide application in adjacent fields suggest that pesticide use may have contributed to die‐offs. That all survivors were hybrids suggests that environmental stress may promote rapid displacement of native genotypes . Efectos Letales de la Calidad del Agua sobre Salamandras de California Amenazadas pero no sobre Salamandras Híbridas Concurrentes

Response of diurnal and nocturnal coral reef fish to protection from fishing: an assessment using baited remote underwater video - E. S. Harvey; S. R. Dorman; C. Fitzpatrick; S. J. Newman; D. L. McLean (Coral Reefs, 2012)

Does proximity to aquatic pollution affect reproductive traits in a wild‐caught intertidal fish? - N. M. Sopinka; J. L. Fitzpatrick; J. E. Taves; M. G. Ikonomou; S. E. Marsh‐Rollo; S. Balshine (Journal of Fish Biology, 2012)
How chronic exposure to aquatic pollution affects reproductive traits was assessed in nesting wild‐caught plainfin midshipman Porichthys notatus in areas with low and high contaminant exposure on Vancouver Island, British Columbia. Males in high‐exposure areas had a greater degree of testicular asymmetry, sperm with shorter heads and fewer live eggs in their nests. The results of this study provide important insights into the potential consequences of contaminant exposure on the reproductive physiology of wild‐caught fishes.

Measuring ecological niche overlap from occurrence and spatial environmental data - Olivier Broennimann; Matthew C. Fitzpatrick; Peter B. Pearman; Blaise Petitpierre; Loïc Pellissier; Nigel G. Yoccoz; Wilfried Thuiller; Marie‐Josée Fortin; Christophe Randin; Niklaus E. Zimmermann; Catherine H. Graham; Antoine Guisan (Global Ecology and Biogeography, 2012)
Aim Concerns over how global change will influence species distributions, in conjunction with increased emphasis on understanding niche dynamics in evolutionary and community contexts, highlight the growing need for robust methods to quantify niche differences between or within taxa. We propose a statistical framework to describe and compare environmental niches from occurrence and spatial environmental data. Location Europe, North America and South America. Methods The framework applies kernel smoothers to densities of species occurrence in gridded environmental space to calculate metrics of niche overlap and test hypotheses regarding niche conservatism. We use this framework and simulated species with pre‐defined distributions and amounts of niche overlap to evaluate several ordination and species distribution modelling techniques for quantifying niche overlap. We illustrate the approach with data on two well‐studied invasive species. Results We show that niche overlap can be accurately detected with the framework when variables driving the distributions are known. The method is robust to known and previously undocumented biases related to the dependence of species occurrences on the frequency of environmental conditions that occur across geographical space. The use of a kernel smoother makes the process of moving from geographical space to multivariate environmental space independent of both sampling effort and arbitrary choice of resolution in environmental space. However, the use of ordination and species distribution model techniques for selecting, combining and weighting variables on which niche overlap is calculated provide contrasting results. Main conclusions The framework meets the increasing need for robust methods to quantify niche differences. It is appropriate for studying niche differences between species, subspecies or intra‐specific lineages that differ in their geographical distributions. Alternatively, it can be used to measure the degree to which the environmental niche of a species or intra‐specific lineage has changed over time.

Attenuation of arthritis in rodents by a novel orally-available inhibitor of sphingosine kinase - Leo R. Fitzpatrick; Cecelia Green; Elizabeth E. Frauenhoffer; Kevin J. French; Yan Zhuang; Lynn W. Maines; John J. Upson; Emmanuel Paul; Henry Donahue; Timothy J. Mosher; Charles D. Smith (Inflammopharmacology, 2011)

Landscape effects on extremely fragmented populations of a rare solitary bee, Colletes floralis - EMILY S. DAVIS; TOMÁS E. MURRAY; ÚNA FITZPATRICK; MARK J. F. BROWN; ROBERT J. PAXTON (Molecular Ecology, 2010)
Globally, there is concern over the decline of bees, an ecologically important group of pollinating insects. Genetic studies provide insights into population structure that are crucial for conservation management but that would be impossible to obtain by conventional ecological methods. Yet conservation genetic studies of bees have primarily focussed on social species rather than the more species‐rich solitary bees. Here, we investigate the population structure of Colletes floralis , a rare and threatened solitary mining bee, in Ireland and Scotland using nine microsatellite loci. Genetic diversity was surprisingly as high in Scottish (Hebridean island) populations at the extreme northwestern edge of the species range as in mainland Irish populations further south. Extremely high genetic differentiation among populations was detected; multilocus F ST was up to 0.53, and and D est were even higher (maximum: 0.85 and 1.00, respectively). A pattern of isolation by distance was evident for sites separated by land. Water appears to act as a substantial barrier to gene flow yet sites separated by sea did not exhibit isolation by distance. C. floralis populations are extremely isolated and probably not in regional migration‐drift equilibrium. GIS‐based landscape genetic analysis reveals urban areas as a potential and substantial barrier to gene flow. Our results highlight the need for urgent site‐specific management action to halt the decline of this and potentially other rare solitary bees.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Cryptic species diversity in a widespread bumble bee complex revealed using mitochondrial DNA RFLPs - Tomás E. Murray; Úna Fitzpatrick; Mark J. F. Brown; Robert J. Paxton (Conservation Genetics, 2008)

The strontium content of roe collected from spawning brown trout Salmo trutta L. reflects recent otolith microchemistry - E. M. Waite; G. P. Closs; J. Kim; B. Barry; A. Markwitz; R. Fitzpatrick (Journal of Fish Biology, 2008)
The relationship between the strontium content of the outer layers of otoliths (an indication of recent marine, estuarine or riverine habitat use) and the strontium content of roe in ripe female brown trout Salmo trutta was examined in fish collected from the Pomahaka River and the lower reaches of the Clutha River, South Island, New Zealand. A close relationship was found between the strontium content of roe and the outer layers of otoliths. This finding suggests that spawned eggs collected from redds could potentially be used to track the extent of upstream spawning migrations by anadromous brown trout.

Building on IUCN Regional Red Lists to Produce Lists of Species of Conservation Priority: a Model with Irish Bees - ÚNA FITZPATRICK; TOMÁS E. MURRAY; ROBERT J. PAXTON; MARK J. F. BROWN (Conservation Biology, 2007)
A World Conservation Union (IUCN) regional red list is an objective assessment of regional extinction risk and is not the same as a list of conservation priority species. Recent research reveals the widespread, but incorrect, assumption that IUCN Red List categories represent a hierarchical list of priorities for conservation action. We developed a simple eight‐step priority‐setting process and applied it to the conservation of bees in Ireland. Our model is based on the national red list but also considers the global significance of the national population; the conservation status at global, continental, and regional levels; key biological, economic, and societal factors; and is compatible with existing conservation agreements and legislation. Throughout Ireland, almost one‐third of the bee fauna is threatened (30 of 100 species), but our methodology resulted in a reduced list of only 17 priority species. We did not use the priority species list to broadly categorize species to the conservation action required; instead, we indicated the individual action required for all threatened, near‐threatened, and data‐deficient species on the national red list based on the IUCN's conservation‐actions template file. Priority species lists will strongly influence prioritization of conservation actions at national levels, but action should not be exclusive to listed species. In addition, all species on this list will not necessarily require immediate action. Our method is transparent, reproducible, and readily applicable to other taxa and regions.

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Seroprevalence Estimation and Risk Factors for A. marginale on Smallholder Dairy Farms in Tanzania - E. S. Swai; E. D. Karimuribo; N. H. Ogden; N. P. French; J. L. Fitzpatrick; M. J. Bryant; D. M. Kambarage (Tropical Animal Health and Production, 2005)

A Cross-sectional Study of Reproductive Performance of Smallholder Dairy Cows in Coastal Tanzania - E. S. Swai; M. J. Bryant; E. D. Karimuribo; N. P. French; N. H. Ogden; J. L. Fitzpatrick; D. M. Kambarage (Tropical Animal Health and Production, 2005)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Plasma Androgen Correlation, EROD Induction, Reduced Condition Factor, and the Occurrence of Organochlorine Pollutants in Reproductively Immature White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster, M. S. Fitzpatrick, G. W. (Archives of Environmental Contamination and Toxicology, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Essential Genes in Autosomal Heterochromatin of Drosophila Melanogaster - D.A.R. Sinclair; S. Schulze; E. Silva; K.A. Fitzpatrick; B.M. Honda (Genetica, 2000)

Life and Death in the Fast Lane: Demographic Consequences of Road Mortality in the Florida Scrub‐Jay - Ronald L. Mumme; Stephan J. Schoech; Glen E. Woolfenden; John W. Fitzpatrick (Conservation Biology, 2000)
We examined the demographic consequences of road mortality in the cooperatively breeding Florida Scrub‐Jay (Aphelocoma coerulescens ), a threatened species restricted to the oak scrub of peninsular Florida. Between May 1986 and July 1995 we monitored the survival and reproductive success of a color‐banded population of jays along a two‐lane highway at Archbold Biological Station. Annual mortality of breeding adults was 0.38 on road territories, significantly higher than the rate of 0.23 for breeders on nonroad territories. High mortality on road territories appeared to be a direct result of automobile traffic per se and not a consequence of road‐induced changes in habitat characteristics. Mortality was especially high for immigrants without previous experience living along the road: in their first two years as breeders on road territories, naive immigrants experienced annual mortality of 0.50 and 0.45. From year 3 onward, however, annual mortality dropped to 0.29, not significantly different from the rate for birds on nonroad territories. This experience‐dependent decline in road mortality could be caused either by surviving jays learning to avoid automobiles or by selective mortality operating through time (demographic heterogeneity). Proximity to the road had no effect on nesting success beyond its indirect effects on breeder experience and group size. Because the mortality of 30‐ to 90‐day‐old fledglings was significantly higher on road territories than on nonroad territories, however, breeder mortality greatly exceeded production of yearlings on road territories. Roadside territories therefore are sinks that can maintain populations of Florida Scrub‐Jays only via immigration. Because Florida Scrub‐Jays do not avoid roadside habitats and may even be attracted to them, road mortality presents a difficult challenge for the management and conservation of this threatened and declining species.

Wound Healing in Earthworms Lumbricus terrestris: A Cellular-Based Biomarker for Assessing Sublethal Chemical Toxicity - M. A. Cikutovic; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman; E. L. Cooper (Bulletin of Environmental Contamination and Toxicology, 1999)

Multi-locus DNA fingerprinting supports genetic monogamy in Florida scrub-jays - James S. Quinn; Glen E. Woolfenden; John W. Fitzpatrick; Bradley N. White (Behavioral Ecology and Sociobiology, 1999)

Studies of the relationship of specific gravity to total solids of potatoes - W. L. Porter; T. J. Fitzpatrick; E. A. Talley (American Journal of Potato Research, 1964)